A Collaborative Approach to Assess Legacy Pollution in Communities Near a Lead–Acid Battery Smelter: The "Truth Fairy" Project. (October 2019) - Johnston, Jill E.; Lopez, mark!; Gribble, Matthew O.; Gutschow, Wendy; Austin, Christine; Arora, Manish
Advocates for civil rights, environmental justice, and movements promoting social justice require data and may lack trust in public authorities, turning instead to academic scientists to help address their questions. Assessing historical exposure to toxic chemicals, especially in situations of a specific industrial source of pollution affecting a community, is critical for informing appropriate public health and policy responses. We describe a community-driven approach to integrate retrospective environmental hazard exposure assessment with community organizing to address concerns about the extent of exposure to toxic metals in a predominantly working-class, Latinx community living near a now-closed lead–acid battery smelter facility. Named the "Truth Fairy Project" by leaders of the community organization East Yard Communities for Environmental Justice, this community–university partnership aimed to assess prenatal and early-life exposures to toxic metals through biomarkers of exposure in baby/deciduous teeth. This partnership integrated community mobilization with empirical research, informing residents about toxic metal exposures and improving the community's capacity to respond to a public health crisis.